2011
DOI: 10.1007/s10457-011-9446-8
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of filamentous fungi in different systems of land use

Abstract: Microbial population and activity can be influenced by changes in the physical and chemical conditions of the soil. The objective of this study was to compare fungal diversity under different agricultural management systems and associated differences in soil properties. This research was carried out in three areas, representing the Atlantic Forest, AFS and cassava (Manihot esculenta Crantz) monoculture system. Five composite samples were collected during the rainy and dry seasons from each area. Using the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Fungi of the genera Aspergillus and Rhizopus are frequently isolated from the Atlantic forest biome (Costa et al 2012, Schoenlein-Crusius et al 2006, Tauk Tornisielo et al 2005, Schoenlein-Crusius & Milanez 1998. The isolation methodology was not intended to recover a maximum number of species, but strains that were easily cultivated in laboratory conditions and prospective amylase producers.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi of the genera Aspergillus and Rhizopus are frequently isolated from the Atlantic forest biome (Costa et al 2012, Schoenlein-Crusius et al 2006, Tauk Tornisielo et al 2005, Schoenlein-Crusius & Milanez 1998. The isolation methodology was not intended to recover a maximum number of species, but strains that were easily cultivated in laboratory conditions and prospective amylase producers.…”
Section: Discussionmentioning
confidence: 99%
“…Richness (R) was estimated by using the number of bands observed in a sample with the Shannon-Wiener diversity index (H') and equitability (E) was calculated using the following equations (Pielou, 1969;Rogers and Tate Iii, 2001;Costa et al, 2012):…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different land-use had no clear effect on these parameters. However, Costa et al (2012) found that plant species substitution could change the quantity and quality of organic matter under decomposition, as the plant residues would be different.…”
Section: Effect Of Different Land-use On Bacterial Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vegetation of the surrounding areas corresponds to Dense Ombrophilous Atlantic Forest (subperennial forest, Costa et al 2012). Annual rainfall in the region is approximately 1700 mm, with two well-defined periods, comprising the dry season from October to March and the rainy period from April to September.…”
Section: The Complex Multistrata Agroforestry Systemmentioning
confidence: 99%